Romance - McBain, Ed, 1926-2005 (Warner Books, 1995)
Detective Bert Kling takes a complaint from actress Michelle Cassidy that someone has been threatening to kill her with a knife. Oddly, she is starring in a play called Romance about an actress who is knifed. Three hours later, Kling learns Cassidy has been stabbed. As he tries to determine if the attack is a publicity stunt, he starts a romance of his own.